2015
DOI: 10.1144/sp428.2
|View full text |Cite
|
Sign up to set email alerts
|

Local tomography model of the northeastern Black Sea: intra-plate crustal underthrusting

Abstract: The Greater Caucasus and southern Crimean Mountains form part of a fold–thrust belt located on the northern margin of the Black Sea, south of the Precambrian craton of eastern Europe. Its southern limit is approximated by the Main Caucasus Thrust, which runs to the west from onshore Russia and Georgia along the whole of the northern margin of the Black Sea. The Main Caucasus Thrust is related to a zone of present-day seismicity along the southern Crimea–Caucasus coast of the Black Sea called the Crimea–Caucasu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
3
0
7
Order By: Relevance
“…A local seismic tomography study of this same area centred on the Kerch Peninsula and reported by Gobarenko et al (2015) complements the Starostenko et al (2016) geophysical study. The resulting three-dimensional P-and S-wave velocity models, for an area of c. 200 × 100 km (east-west and north-south, respectively) with a depth of c. 40 km ( Fig.…”
Section: 'Black Sea' Domain Of the Eastern Black Sea -Caucasus Tectonsupporting
confidence: 55%
See 2 more Smart Citations
“…A local seismic tomography study of this same area centred on the Kerch Peninsula and reported by Gobarenko et al (2015) complements the Starostenko et al (2016) geophysical study. The resulting three-dimensional P-and S-wave velocity models, for an area of c. 200 × 100 km (east-west and north-south, respectively) with a depth of c. 40 km ( Fig.…”
Section: 'Black Sea' Domain Of the Eastern Black Sea -Caucasus Tectonsupporting
confidence: 55%
“…Cavazza et al (2015) suggest a final (and contemporaneous) phase of the Arabia -Eurasia collisional process to have started in the Miocene, mainly expressed today as the active Anatolian Fault/westwards extrusion of Anatolia. Gobarenko et al (2015) infer, however, that contemporary earthquakes on the northern margin of the eastern Black Sea provide evidence for continued underthrusting of Black Sea crust and lithosphere beneath the Crimean (Kerch) and Taman peninsulas. They also suggest from their local tomography velocity models that the underthrust Black Sea is not of oceanic affinity.…”
Section: Synthesis and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Была опре 100 делена структура земной коры, включая рельеф поверхности Мохо [Москаленко, Маловицкий, 1974]. Через 36 лет были опуб ликованы результаты переинтерпретации этих данных с использованием первичных сейсмограмм и годографов из старых от четов и публикаций с применением про цедуры трассирования лучей [Yegorova et al, 2017]. При этом в строении кристалли ческой коры не было установлено прин ципиальных различий от оригинальных ре зультатов, полученных ручным способом [Starostenko et al, 2010].…”
unclassified
“…В Азовском море не достигнуто консен суса относительно границы Восточно-Ев ропейской платформы (ВЕП) и Скифской плиты (СП), возраста кристаллического фундамента СП и тектонического р ай о нирования. В северо-восточной части ВЧВ тип коры определен неоднозначно Gobarenko et al, 2017].…”
unclassified